Potential role of the flower mite Hattena rhizophorae (Mesostigmata: Ameroseiidae) on Rhizophora mangle pollination - Ruiz, Tania Carolina Hoyos; Montoya-Pfeiffer, Paula María [UNESP] (Springer Nature, 2025)
Flower mites are often assumed to negatively impact plant reproductive fitness by depleting floral resources for pollinators. However, there is a lack of studies directly investigating the effects of mites on pollination. This study explores the potential role of Hattena rhizophorae mites in the pollination of the anemophilous species Rhizophora mangle. We hypothesized that H. rhizophorae mites might contribute to the pollination of R. mangle if they (1) are prevalent on flowers, (2) can easily disperse through means other than phoresy, and (3) contribute to pollen transport and deposition. We examined the spatiotemporal variability of H. rhizophorae mites on R. mangle flowers in relation to the season, the R. mangle patch size, and the abundance of insect visitors that may act as their dispersal vectors We also investigated whether mites could alternatively disperse among flowers via air currents and running water, quantified the pollen grains on the mites’ bodies, and observed whether they made contact with the flower stigmas. We found that mites might serve as pollinators of R. mangle as they were relatively common on flowers, with an average infestation frequency of 40% ± 7% of flowers and an abundance of 68.4 ± 15.5 mites per flower. Their numbers increased with patch size, insect visitor abundance, and during the rainy season. Mites were transported by wind, though there was no evidence of transportation by running water. They appeared to contribute to pollen transport and deposition, as we observed pollen grains attached to their bodies and mites walking on flower stigmas.
Keywords: Flower mites; Hattena rhizophorae; Mangrove ecosystems; Mite dispersal; Pollination; Rhizophora mangle